Adaptive response‐dependent two‐phase designs: Some results on robustness and efficiency. (7th July 2022) - Yang, Ce; Diao, Liqun; Cook, Richard J.
Abstract : Large cohort studies now routinely involve biobanks in which biospecimens are stored for use in future biomarker studies. In such settings, two‐phase response‐dependent sampling designs involve subsampling individuals in the cohort, assaying their biospecimen to measure an expensive biomarker, and using this data to estimate key parameters of interest under budgetary constraints. When analyses are based on inverse probability weighted estimating functions, recent work has described adaptive two‐phase designs in which a preliminary phase of subsampling based on a standard design facilitates approximation of an optimal selection model for a second subsampling phase. In this article, we refine the definition of an optimal subsampling scheme within the framework of adaptive two‐phase designs, describe how adaptive two‐phase designs can be used when analyses are based on likelihood or conditional likelihood, and consider the setting of a continuous biomarker where the nuisance covariate distribution is estimated nonparametrically at the design stage and analysis stage as required; efficiency and robustness issues are investigated. We also explore these methods for the surrogate variable problem and describe a generalization to accommodate multiple stages of phase II subsampling. A study involving individuals with psoriatic arthritis is considered for illustration, where the aim is to assess the association between the biomarker MMP‐3 and the development of joint damage.